2016
DOI: 10.1242/jcs.185363
|View full text |Cite
|
Sign up to set email alerts
|

Two classes of matrix metalloproteinases reciprocally regulate synaptogenesis

Abstract: Synaptogenesis requires orchestrated intercellular communication between synaptic partners, with trans-synaptic signals necessarily traversing the extracellular synaptomatrix separating presynaptic and postsynaptic cells. Extracellular matrix metalloproteinases (Mmps) regulated by secreted tissue inhibitors of metalloproteinases (Timps), cleave secreted and membrane-associated targets to sculpt the extracellular environment and modulate intercellular signaling. Here, we test the roles of Mmp at the neuromuscul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 30 publications
2
27
0
Order By: Relevance
“…4) (Endo et al, 2003;Wang and Page-McCaw, 2014). Mutations in two metalloproteinases (Mmps) caused the localization of glypican to be more restricted (Mmp1) or broader (Mmp2) at the NMJ (Dear et al, 2016). The defects in synapse formation and function in Mmp1 mutants (more restricted expression of glypican) or Mmp2 mutants (broader expression) could be rescued by overexpression of ectopic glypican or removing a copy of glypican, respectively (Dear et al, 2016).…”
Section: Hs In Synaptic Patterning and Functionmentioning
confidence: 99%
“…4) (Endo et al, 2003;Wang and Page-McCaw, 2014). Mutations in two metalloproteinases (Mmps) caused the localization of glypican to be more restricted (Mmp1) or broader (Mmp2) at the NMJ (Dear et al, 2016). The defects in synapse formation and function in Mmp1 mutants (more restricted expression of glypican) or Mmp2 mutants (broader expression) could be rescued by overexpression of ectopic glypican or removing a copy of glypican, respectively (Dear et al, 2016).…”
Section: Hs In Synaptic Patterning and Functionmentioning
confidence: 99%
“…It remains unclear how octopamine signaling at type I synaptic regions regulates postsynaptic Dlp levels. Broadie and collaborators revealed that ECM metalloproteinases (Mmp1 and Mmp2) and the tissue inhibitor of metalloproteinases (Timp) play critical roles in synapse formation and activity-dependent plasticity in the Drosophila NMJ (Dear et al, 2016(Dear et al, , 2017Shilts and Broadie, 2017). Mmp2 from the presynaptic and postsynaptic compartments has been shown to negatively regulate synaptic Dlp levels at the NMJ, possibly by the proteolytic cleavage of Dlp core proteins (Wang and Page-McCaw, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Mmp2 from the presynaptic and postsynaptic compartments has been shown to negatively regulate synaptic Dlp levels at the NMJ, possibly by the proteolytic cleavage of Dlp core proteins (Wang and Page-McCaw, 2014). However, Mmp1 is known to associate with Dlp via heparan sulfate (HS) chains and positively regulate Dlp expression levels at type I endings (Dear et al, 2016). Octopamine signaling after food deprivation may activate the proteolytic activity of Mmp2 at type I synaptic regions, leading to a decrease in postsynaptic Dlp levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibodies used were: mouse anti-Wg (DSHB 1:50), mouse anti-Repo (DSHB 1:50), mouse anti-Fz1 (DSHB 1:50), mouse anti-Cyt-Arm (DSHB 1:50), mouse anti-MMP1 (DSHB 5H7B11, 3A6B4, 3B8D12, 1:50), rabbit anti-MMP2 (1:500, K. Broadie) [85], guinea pig anti-grnd (1:250, P. Leopold) [75], mouse anti-β-galactosidase (Sigma, 1:500), rabbit anti-GFP (Invitrogen A11122, 1:500), mouse anti-GFP (Invitrogen A11120,…”
Section: Antibodies For Immunofluorescencementioning
confidence: 99%